Unintended consequences: food prices increase in an Arctic indigenous community amidst road infrastructure development and loss of federal freight subsidy - Tiff-Annie, Kenny; Nicholas, Li; Kim, Mathieu; Charmaine, Teddy; Sonia, Wesche; Jullian, MacLean; Celina, Wolki (Frontiers in Nutrition, 2025)
IntroductionRoad infrastructure development is often promoted as a strategy to reduce food insecurity in remote Arctic communities. However, the real-world impacts of such investments—particularly when tied to the withdrawal of food access supports such as the Nutrition North Canada (NNC) freight subsidy, which is provided to retailers to offset high transportation costs—remain poorly understood. This study examines the effects of the Inuvik–Tuktoyaktuk Highway opening and the concurrent loss of the NNC freight subsidy on food prices in Tuktoyaktuk, Northwest Territories.MethodsWe used a quasi-experimental difference-in-differences design comparing Tuktoyaktuk (intervention community) to Aklavik (control community). Data sources included participatory food costing surveys, Northwest Territories Community Price Index data, and retailer-reported Nutrition North Canada price data. Analyses assessed trends in the Revised Northern Food Basket cost and individual product prices over time, using both aggregate and dynamic difference-in-differences models.ResultsPrior to the opening of the Inuvik–Tuktoyaktuk Highway in November 2017, food prices in Tuktoyaktuk and Aklavik were closely aligned. Following the road’s construction and the withdrawal of full Nutrition North Canada subsidies for Tuktoyaktuk, prices in the community began to rise. Although prices initially remained stable, a significant divergence emerged over time: by March 2022, food prices in Tuktoyaktuk were nearly 20% higher than in Aklavik. Improved surface access did not reduce the price of non-subsidized goods, as anticipated. Freight savings, if realized, were minimal or not consistently passed on to consumers. The principal driver of food price increases appears to be the loss of ongoing freight supports, particularly as neighboring Aklavik benefitted from new NNC enhancements that Tuktoyaktuk no longer accessed.ConclusionInfrastructure alone is insufficient to improve food affordability in remote Indigenous communities. Retailer pricing discretion and market dynamics may mediate the impacts of transportation investments. To avoid exacerbating food insecurity, infrastructure projects must be accompanied by dynamic monitoring, community-driven food security strategies, and policy frameworks based on real affordability metrics rather than proxy indicators like road access. Strengthening both market and country food systems is critical to supporting Indigenous food sovereignty and resilience.